Penurunan Kecemasan melalui Senam Prolanis Pada Lansia - Ike Prafitasari; Nurul Mawaddah; Oktovian Dwi Arini (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
Indonesia has reached the phase of the old structured country because it has an elderly population which reaches 9.27% ​​of the total population. Problems experienced were increasing due to the prevalence in the elderly due to decrease capability of physical and mental. Prolanist exercises a form of physical exercise that was overcoming adversity in the elderly. This study aimed to study the effect of prolanist exercises on anxiety in the elderly in the working area of ​​the Sumberbaru Health Center. The design of this study was pre-experimental with a total sampling technique with a total sample of 29 prolanist members. Analysis of the data used was a paired t-test statistical test. The results obtained before prolanis exercises most of the elderly were at mild anxiety levels, with an average HARS score of 19.76. After prolanis exercises the elderly anxiety almost half are in the level of mild anxiety, with an average HARS score of 18.10. Based on statistical tests with a significance level of α = 0.05, the results obtained p value 0,000. Because the value of p <α (0.05), Ho was rejected. So there was an effect prolanist exercises for anxiety the elderly at the Sumberbaru Health Center. Prolanis exercises activities created social interaction between the elderly so that the elderly cannot feel isolated. Prolanis exercises also increase oxygen absorption, pain management, and trigger endorphins to created a sense of calm thereby reducing anxiety in the elderly.